Effect of Motivation and Work Experience on Employee Performance at PT. Raja Sakti Bandung - Kosasih Kosasih (Peneliti.net, 2019)
This study aims to determine the effect of motivation and work experience on employee performance at PT. Raja Sakti Bandung. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that motivation has a significant effect on employee performance by 44.7%, hypothesis testing is obtained t count > t table or (8.894 > 1.984). Work experience has a significant effect on employee performance by 38.1%, hypothesis testing is obtained t count > t table or (7,767 > 1,984). Motivation and work experience simultaneously have a significant effect on employee performance with the regression equation Y = 10.207 + 0.409X1 + 0.345X2 and the contribution of influence is 51.8%, hypothesis testing is obtained F count > F table or (52.134 > 2,700).